GYMNOSPERMIUM ALTAICUM (PALL.) SPACH (BERBERIDACEAE), AN EARLY SPRING ELEMENT OF WILD FRUIT FORESTS OF THE TRANS-ILI ALATAU (Experimental biology, 2021)
The floristic composition of communities of apple and hawthorn forests with the participation of the rare species Gymnospermium altaicum (Pall.) Spach was studied in the Trans-Ili (Zailiyskiy) Alatau . The list of higher plants includes 156 species from 121 genera and 48 families. Most of them (84%) are herbaceous plants; there are 25 tree and shrub species, nine of which are wild non-native species. Representatives of ten families make up 65% of the total number of species. The floristic core of the surveyed communities consists of 39 species, which mainly belong to the group of forest and forest-meadow ecological elements. Also other rare species listed in the Red Book of Kazakhstan, Malus sieversii, Armeniaca vulgaris and Paeonia intermedia, were found in these communities. We noticed signs of anthropogenic disturbance in the studied communities, including the presence of  adventive and wild non-native species. We recommend to organize regular monitoring and strengthen the protection of the communities surveyed.Key words: Gymnospermium, Berberidaceae, Red Data Book of Kazakhstan, plant communities, floristic composition, Trans-Ili Alatau.